Factors affecting Maillard induced gelation of protein-sugar systems - Azhar, Mat Easa (1996)
Gelation due to the Maillard reaction took place when solutions containing a low level of bovine serum albumin were heated in the presence of carbonyl compounds. The Maillard reaction caused a change in colour, a decrease in the pH and induced gelation. These changes were dependent on the type and concentration of sugars or protein and on the heating conditions used. Reducing sugar and Maillard reaction products (e.g. glyoxal) affected these changes, yet their order of reactivity for browning and gelation were not necessarily the same. Loss of available lysine and arginine plus changes in the thio amino acids showed that these were implicated in the reaction.